Participação dos canais de potássio na ação espasmolítica de Solanum agrarium Sendtner em íleo de cobaia e útero de rata - Correia, Ana Carolina Carvalho (2009)
Solanum agrarium Sendtner known popularly as babá , gogóia , and melancia da praia . In folk medicine, the decoction of its roots is used as abortive (AGRA, 1991). In a preliminary study, Santos et al. (2003) demonstrated that crude ethanolic extract of aerial parts from S. agrarium (SA-EtOH) showed non-selective spasmolytic activity on guinea-pig ileum and rat uterus. The aim of the study was evaluate on the cytotoxic potential of SA-EtOH in rats erythrocytes and to investigate the spasmolytic action mechanism on guinea-pig ileum and rat uterus. SA-EtOH extract showed moderate hemolytic activity only at concentration of 243 and 500 μg/mL (Emax = 21.2 ± 3.2%). On guinea-pig ileum, SA-EtOH extract inhibited the cumulative concentration-response curves to carbachol (CCh) and histamine, and these were shifted to the right, in a non-parallel manner, with depression of the maximal effect (Emax), suggesting a noncompetitive antagonism. SA-EtOH extract relaxed in a significant and concentration dependent manner the ileum pre-contracted with 40 mM KCl (EC50 = 17.4 ± 3.5 μg/mL), 10-6 M CCh (EC50 = 119.4 ± 24.3 μg/mL) or 10-6 M histamine (EC50 = 18.7 ± 4.6 μg/mL), suggesting that SA-EtOH extract could be acting on voltage-gated Ca2+ channels (Cav). This assumption was confirmed by observation that SA-EtOH extract antagonized the CaCl2 induced contractions in the depolarizing medium without Ca2+. The finding that SA-EtOH extract relaxed (EC50 = 187.2 ± 27.3 μg/mL) the guinea-pig ileum pre-contracted with S-(-)-BAY K8644 suggests that the Ca2+ channel subtype involved is the CaV1. As the SA-EtOH extract was more potent in relaxing the body pre-contracted with KCl than by S-(-)-Bay K8644, it is suggestive of indirect blockade of the Cav1. We decided to investigate the participation of K+ channels in the spasmolytic action of SA-EtOH extract. The relaxation curve induced by SA-EtOH extract was rightward displacement only in the presence of tetraethylammonium (TEA+) 1 mM, this concentration is a selective blocker of the large conductance clacium-activated K+ channels (BKca) (EC50 = 37.7 ± 4.9 μg/mL) and 4-aminopyridine, selective blocker of the voltage activated K+ channels (Kv) (EC50 = 48.9 ± 6.2 μg/mL). On rat uterus, SA-EtOH extract inhibited the cumulative concentration-response curves to oxytocin, and these were shifted to the right, in a non-parallel manner, with depression of the maximal effect (Emax) suggesting a noncompetitive antagonism. SA-EtOH extract did not effective at relax the uterus pre-contracted with 60 mM KCl (Emax = 10.5 ± 5.0%), however relaxed in a significant and concentration dependent manner the rat uterus pre-contracted with 10-2 UI/mL (EC50 = 56.3 ± 8.2 μg/mL). Therefore, suggesting that SA-EtOH extract could be promoting its spasmolytic effect of indirect blockade influx Ca2+ by Cav, as observed in guinea-pig ileum. However, the relaxation curve induced by SA-EtOH extract was rightward displacement only in the presence of glibenclamide (EC50 = 124.8 ± 21.0 μg/mL), selective blocker of the ATP-sensitive K+ channels (KATP), different from that observed in guinea-pig ileum. These results suggest that SA-EtOH extract is not promoting the membrane injury on rat erythrocytes and that the spasmolytic action mechanism of SA-EtOH extract involves modulation/activation of BKCa and KV on guinea-pig ileum, and of KATP on rat uterus.